Pelaporan sebagai Prinsip Akuntabilitas dalam Islam: Analisis al-Qur’an, Hadis, dan Pemikiran Ulama - Abdul Muhyi; Nur Arfiyah Febriani (Lembaga Yasin AlSys, 2026)
Although reporting practices have long been an important part of human life, both in vertical relations with Allah and in horizontal relations with fellow human beings, systematic studies that examine reporting as a manifestation of moral, ethical, and social accountability from an Islamic perspective remain relatively limited. This article aims to analyze the concept of reporting in Islam based on verses of the Al-Qur’an, the hadiths of the Prophet Muhammad, and the interpretations of classical and contemporary scholars. The method used is library research with a qualitative analytical approach through an examination of Al-Qur’an texts, hadiths, tafsir works, and modern academic literature on accountability. The findings show that reporting in Islam encompasses three main dimensions: (1) human accountability to Allah, which is absolute and unavoidable; (2) reporting to fellow human beings, which emphasizes honesty, justice, and transparency; and (3) regulatory principles of reporting, which include the prohibition of falsehood, the obligation of tabayyun, and the preservation of trust (amānah). This concept is relevant to contemporary reporting practices in the governance of public institutions, organizations, and educational establishments because it provides a normative framework that guides the formation of fair and transparent reporting mechanisms. Thus, Islam offers a comprehensive foundation for building a culture of accountability that is just and integrity-based across various domains of modern life.